Urethral fistula repair, including urethral elongation and an anti-incontinence procedure - a case report - Thinagrin D. Naidoo (Elsevier, 2023)
Vesicovaginal fistula remains a significant cause of female urinary incontinence and impaired quality of life worldwide. Urethral-vaginal fistulas are less common, and difficult to manage, posing difficulties in terms of diagnostic evaluation, the surgical approach to closure, and how the associated complication of stress urinary incontinence is addressed. In this case report the management of a 34-year-old woman who presented with a urethral fistula following initial surgery for a urethral abscess is presented, including fistula closure; lengthening of the urethra; and addressing the loss of sphincter function. This case highlights the fact that a successful outcome in these patients depends on proper surgical technique, and the experience and skill of the management team.